Impacto de aplicação do lodo de indústria de gelatina em colunas de solo e no percolado - Tonello, Anna Paola (2014)
The reuse of water from food industries of animal and vegetable origin, as a source of water, nutrients and organic matter to the soil and plants is a practice traditionally employed in agriculture and should be treated analogously to the fertigation. However, high application riles can lead to accumulation of elements such as sodium in the soil, and generate impacts on the environment. Given this problem, this work aims to evaluate the effect of application of increasing doses of sludge on gelatin industry (LIG): chemical soil and leachate and response of com plants. Experiment was conducted in a greenhouse in columns with Distroferric AIfisol and Oxisol, the experiment was arranged in a completely randomized design with three replicates. The doses of sludge industry gelatin were 0, 150, 300, 450 and 600 m3 ha-i The collection of the leachate was carried out on three dates. After two weeks of applying sludge on maize (Zea maus L.) were sown. Concluded that pH, and carbon concentrations of Ca2+, Mg2+, K+ in the soil decreased in relation to the Latossolo Nitosol with increasing doses of the LIG. The phosphorus content in the soil increased as the high rates of LIG, especially in the superficial layers. The electrical conductivity (CE) in soil and leachate increased with herbicide application, however the Oxisol showed lower CE, due to greater loss of anions. The concentration of Na in the soil and in the leachate increased with the application of LIG. The pH increased during the experimental period and the concentrations of Caz+, Mg2+, K+ in the leachate increased with application of doses of LIG. The leaf area index decrease with increasing doses and dry matter was higher in the Oxisol. The sodium adsorption ratio was classified for the two sons as low salinity.